AN INSIGHT OF NEED ANALYSIS IN ARABIC FOR ISLAMIC TOURISM IN KUALA LUMPUR CITY CENTRE BASED ON NAQLI AND AQLI MODEL - Jaffar, Mohammad Najib; Zainuddin, Nurkhamimi; Abdul Hamed, Kirembwe Rashid; Sahrir, Muhammad Sabri (2019)
Malaysia is among popular destination among Islamic tourists all over the world due to its Islamic environment and society. According to Tourism Malaysia, Malaysia has been chosen as the world's top destination for Muslim travellers for three consecutive years in recent surveys conducted by Singapore's Crescent Rating and the United States' Dinar Standard. Hence, this study is conducted to explore needs analysis in Arabic for Islamic Tourism through an integration of Naqli and Aqli model which is a combination between revealed and conventional knowledge. This study was implemented in Kuala Lumpur city centre as it is the center of tourists among selected purposive sampling of 30 respondents of the Arab tourists. The main findings of this study can be viewed from various aspects; Among the main factors of Saudi tourist attractions to Malaysia is lawful and Sharia-compliant hotels, facilities and products. From the perspective of Arabic language use, there are some deficiencies and loopholes that can be fixed. Yet from the aspect of the tourists‟ needs suggestions pertaining to the use of Arabic language were identified. While in terms of the necessities for Arabic for Islamic Tourism learning module, the topics need to be appropriate and more emphasis should be focused on communication aspect.